Cancer-associated fibroblasts-derived exosomal miR-17-5p promotes colorectal cancer aggressive phenotype by initiating a RUNX3/MYC/TGF-β1 positive feedback loop. (28th October 2020) - Zhang, Yue; Wang, Shanci; Lai, Qiuhua; Fang, Yuxin; Wu, Changjie; Liu, Yongfeng; Li, Qingyuan; Wang, Xinke; Gu, Chuncai; Chen, Junsheng; Cai, Jianqun; Li, Aimin; et al.
Abstract: Cancer-associated fibroblasts (CAFs) are the main stromal cells in the tumour microenvironment (TME). We found that the distribution of CAFs was significantly increased with tumour progression and led to a poor prognosis. In vitro and in vivo assays revealed that CAFs enhanced colorectal cancer (CRC) metastasis. Based on extraction and identification of exosomes of CAFs and normal fibroblasts (NFs), CAFs-exo showed higher expression of miR-17-5p than NFs-exo and could deliver exosomal miR-17-5p from parental CAFs to CRC cells. Further exploration verified that miR-17-5p influenced CRC metastasis capacity and directly targeted 3′-untranslated regions (UTRs) of RUNX family transcription factor 3(RUNX3). Our findings further revealed that RUNX3 interacted with MYC proto-oncogene(MYC) and that both RUNX3 and MYC bound to the promoter of transforming growth factor beta1(TGF-β1) at base pairs 1005–1296, thereby activating the TGF-β signalling pathway and contributing to tumour progression. In addition, RUNX3/MYC/TGF-β1 signalling sustained autocrine TGF-β1 to activate CAFs, and activated CAFs released more exosomal miR-17-5p to CRC cells, forming a positive feedback loop for CRC progression. Taken together, these data provide a new understanding of the potential diagnostic value of exosomal miR-17-5p in CRC. Highlights: The distribution of CAFs was frequently up-regulated in aggressive clinical CRC tissues and associated with poor prognosis CAFs promoted CRC aggressive phenotype via activating exosomal miR-17-5p/RUNX3/MYC axis. RUNX3 and MYC co-activated TGF-β signalling pathway and formed a positive feedback loop for CRC progression.